THE INFLUENCE OF SOCIAL MEDIA MARKETING, PROMOTION, AND SERVICE QUALITY ON CUSTOMER SATISFACTION AND ITS IMPLICATIONS ON REPURCHASE INTENTION AT RAMEN YA RESTAURANT! - Stella, Josephine; Marvianta, YB Andre (Ikatan Dosen Menulis, 2026)
Indonesia recorded approximately 215.63 million internet users during the 2022–2023 period, with an increasing marketing opportunity through social media, particularly among Generation Z and millennials. Ramen is the second-favorite food. This research is intended to analyze the impact of social media marketing, promotion, and service quality on customer satisfaction. and its implications for repurchase intention at Ramen Ya! restaurant. Respondents are individuals residing in Jakarta, Bogor, Tangerang who have visited Ramen Ya! The study utilizes the AMOS 5.0 program data analysis was conducted using Structural Equation Modeling (SEM). Purposive sampling and non-probability sampling techniques are chosen, with a total of 292 respondents. The results indicate that Social Media Marketing, Promotion, and Service Quality do not affect Repurchase Intention. However, Promotion and Service Quality significantly and positively influence Customer Satisfaction, ultimately affecting Repurchase Intention. In conclusion, enhancing promotion and service quality is crucial to elevate customer satisfaction, while improving social media marketing is essential for fostering repurchase intention. Recommendations for enhancing customer satisfaction include collecting direct feedback on promotions, providing samples of new menu items, and ensuring employees possess excellent communication skills. Additionally, improving social media marketing, offering exclusive discounts, and conducting customer surveys with voucher incentives can boost repurchase intention.